Food waste and disposal behaviour among university students / Soo-Cheng Chuah and JS Keshminder Singh - Chuah, Soo-Cheng; JS, Keshminder Singh (Faculty of Business and Management, UiTM Shah Alam, 2020)
Food waste is a crucial and persistent issue globally. The household food waste phenomenon in Malaysia has emerged as increasingly serious with the rapid rise in its generation by domestic households. This study explored youth behaviour toward food waste and its disposal behaviour among the university students of Faculty Business and Management, Universiti Teknologi MARA, Puncak Alam Campus. Factor analysis was applied to identify the underlying factors of food waste and disposal behaviour, while the independent t-test served to examine gender differences regarding the factors. In particular, Pearson's Chi-square Test of Independence was applied to examine the association between gender and food waste, food planning, and food recycling behaviors. To this end, a self-administrated questionnaire was used to collect data based on the convenience sampling method in which a sample size of 111 respondents were engaged with. Factor analysis successfully identified three factors as a result, namely food disposal, knowledge of food waste, and involvement in preventing food waste. The independent t-test also revealed significant gender differences among the students on food disposal behavior, whereas no significant gender differences were found with the factors of knowledge of food waste and involvement in preventing food waste. Additionally, there was no association between gender and food recycling, food planning, and food waster behaviours, respectively. As such, these findings can increase student participation and commitment to reducing food waste as it is fast becoming an issue for all.